Ecclesia semper reformanda: Protestant Principle and Church Renewal - Jeanrond, Werner G. (Dansk Teologisk Tidsskrift, 2010)
Paul Tillich’s dialectics of “Protestant principle” and “Catholic substance” acknowledges the need to question any form of embodiment and inculturation of Christian faith in the transcendent and sovereign God, i.e. it acknowledges the necessity of both continuing church renewal and continuing religious and cultural embodiment of the Christian gospel. This article explores the theological potential of these concepts with regard to both the eschatological nature of Christian faith praxis and the mulitireligious universe in which Christian hope for God’s coming reign must articulate itself today.